The management of community development projects by the District Development Committee : a case of Mahalapye Sub District in Botswana - Mapitse, Thobo Gloria (University of Limpopo (Turfloop Campus), 2009)
The Mahalapye sub District Development Committee is the most significant organization in the sub district as it sets overall goals, direction and priorities with which all development initiatives within the district should conform to. The membership of the committee includes all heads of central and local government departments, government planners, heads of Parastatals, and representatives of Non Governmental Organisations (NGOs). Effective management of projects requires collective consciousness, effort and will and it is important that members of the sub District Development Committee work as a team to ensure that all projects are implemented within the set time frames and limited resources. The development challenges facing Mahalapye sub district are complex. These challenges are not peculiar to the sub district, but are also a challenge to other districts in Botswana. These challenges include the need to implement village infrastructure projects in a cost effective manner in that the projects are completed within the estimated budget and time schedule. The research findings are that indeed the problem of project cost and time overruns is a problem in Mahalapye sub District and that the problem is attributed to the way the projects are managed, in particular, by the sub District Development Committee. A number of recommendations have been provided to help overcome the problem
Thesis (MPA) --University of Limpopo, 2009
Keywords: Community development; Economic development; Community development -- Botswana; Economic development